Quality Assurance Systems in the Development of Fishery Product Processing MSMEs: Sistem Penjaminan Mutu dalam Pengembangan UMKM Pengolahan Hasil Perikanan - Maghfira, Nadya Permata; Aini, Nur; Arsil, Poppy; Arsyistawa, Hadana Sabila (JITIPARI, 2024)
The quality standards of processed fishery products can be assessed by applying regulations required in the industry, including halal certification and quality assurance systems. The implementation of halal certification and quality assurance system regulations can increase the development of MSMEs, especially with Law Number 33 of 2014 concerning the Halal Assurance System, which requires halal food to be halal certified. One of the factors that cause most MSMEs not to implement halal certification and other regulations is the existence of internal and external problems. This study aims to develop a development strategy for fishery product processing MSMEs by analyzing internal and external factors in implementing halal certification and quality assurance systems. The Quantitative Strategic Planning Matrix (QSPM) method is used to prioritize alternative strategies based on the SWOT analysis results. This research concludes that the priority strategy for developing fish processing MSMEs is the SO strategies, which include utilizing government programs to form marketing and distribution networks, innovating attractive product packaging following people's lifestyles, utilizing technological advances for promotional activities, marketing, and expanding marketing networks and the need to create a business website so that the market can recognize every product owned by the company.